2021
DOI: 10.3389/fimmu.2021.661162
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational and Therapeutic Control of Gasdermin-Mediated Pyroptosis and Inflammation

Abstract: Pyroptosis is a proinflammatory form of cell death, mediated by membrane pore-forming proteins called gasdermins. Gasdermin pores allow the release of the pro-inflammatory cytokines IL-1β and IL-18 and cause cell swelling and cell lysis leading to release of other intracellular proteins that act as alarmins to perpetuate inflammation. The best characterized, gasdermin D, forms pores via its N-terminal domain, generated after the cleavage of full length gasdermin D by caspase-1 or -11 (caspase-4/5 in humans) ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 101 publications
(162 reference statements)
0
31
0
Order By: Relevance
“…Canonical and noncanonical pyroptosis are associated with GSDMD cleavage. The N-terminal fragment of GSDMD (GSDMD-NT) binds phospholipids on the plasma membrane and oligomerizes to form functional pores [ 40 ]. GSDMD pore formation causes mitochondrial dysfunction, cell ballooning, cell rupture, IL-1 β release, and eventually the release of high mobility group 1 protein and ASC specks [ 36 , 40 ].…”
Section: Relevance Of Pyroptosis In Corneal Diseasesmentioning
confidence: 99%
“…Canonical and noncanonical pyroptosis are associated with GSDMD cleavage. The N-terminal fragment of GSDMD (GSDMD-NT) binds phospholipids on the plasma membrane and oligomerizes to form functional pores [ 40 ]. GSDMD pore formation causes mitochondrial dysfunction, cell ballooning, cell rupture, IL-1 β release, and eventually the release of high mobility group 1 protein and ASC specks [ 36 , 40 ].…”
Section: Relevance Of Pyroptosis In Corneal Diseasesmentioning
confidence: 99%
“…Pyroptosis is one of the main mechanisms of cell death and causes an acute inflammatory response by activating inflammasomes and releasing inflammatory cytokines (7). Previous studies have demonstrated that pyroptosis is involved in the occurrence and development of infectious diseases, cardiovascular diseases, cancer and numerous other diseases (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of NLRP3 is regulated transcriptionally, to control messenger RNA (mRNA) expression ( 16 , 17 ), posttranscriptionally, to control mRNA stability ( 18 ), and by several posttranslational modifications (PTMs), to control protein activity ( 8 , 19 ). The latter are critical especially in chronic conditions where persistent NLRP3 expression occurs and NLRP3 transcriptional control is lost ( 20 22 ).…”
mentioning
confidence: 99%